Efektivitas Pembelajaran Kooperatif Tipe Team Games Tournament Berbantuan Crossword Puzzle terhadap Hasil Belajar Siswa pada Pembelajaran IPA di SDN Triwung Lor 2 - Ary Analisa Rahma; Utami Ratna Swari; Hermin Arista; Indah Noor Dwi Kusuma Dewi; Wahyu Nur Achmadin (Journal on Education, 2024)
This study aims to determine the effectiveness of cooperative learning type Team Games Tournament assisted by crossword puzzle on students’ learning outcomes in science learning at SDN Triwung Lor 2. The use of learning models through educational games is designed so students are able to improve their questioning, writing, discussion, and collaboration skills. This study used a quantitative approach with a pre-experimental research method and a one group pretest-posttest research design, the research subjects amounted to 10 students determined by purposive sampling. The research data analysis was carried out by paired samples t-test on the SPSS 26 program, the results of the study can be concluded that the cooperative learning model Team Games Tournament assisted by crossword puzzle is quite effective to be used to improve student learning outcomes in science learning at SDN Triwung Lor 2.